The Impact of Institutional Quality on Environmental Quality: A Time-Series Analysis of Bangladesh (1996-2015) - Toufique, Mohammad Mokammel Karim (Universitas Airlangga, 2025)
This paper examines the influence of institutional quality on environmental quality in Bangladesh from 1960 to 2015. While institutional quality is the primary explanatory variable, GDP and natural gas electricity consumption are included as moderating variables to control for economic activity and energy-related influences on the environment. The study utilizes the autoregressive distributed lag (ARDL) bounds testing approach and the Toda-Yamamoto (T-Y) Granger causality test to analyze the association. Two measures of institutional quality are developed. One is a composite index constructed from the Worldwide Governance Indicators (WGIs) using principal component analysis (PCA). The other is the average of the six WGIs. Regardless of the index, the findings indicate that higher institutional quality helps reduce CO2 emissions. On the contrary, both GDP and ENG tend to increase CO2 emissions. The ARDL bounds test results confirm the existence of a long-run relationship among the variables in both models. Policymakers need to concentrate on improving institutions to improve environmental quality. Concurrently, they must ensure that economic progress and electricity generation production are sustainable in Bangladesh.